A retrospective analysis of outcome of endoscopic management in choledocholithiasis in a tertiary care centre - Shah, Dhvani; Mahey, Rajesh; Dharap, Satish; Chilbule, Priyanka; Deka, Hiranya (International Surgery Journal, 2022)
Background: The role of endoscopic retrograde cholangiopancreatography (ERCP) as a therapeutic intervention for choledocholithiasis is long established. Endoscopic therapy involves stone extraction using conventional methods after performing endoscopic biliary sphincterotomy. The objective of this study was to determine the outcome of patients with choledocholithiasis being treated in our setup. Methods: This retrospective observational study was conducted at T.N.M.C. and BYL Nair Hospital, Mumbai from January 2017 to October 2017. All patients with choledocholithiasis proven radiologically were admitted. All patients underwent elective endoscopic retrograde cholangiopancreatography. In patients in whom ERCP failed, open surgical clearance of the common bile duct was done. Results: A total of 50 cases of choledocholithiasis were admitted during the study period. Age distribution in our study was from 27 years to 81 years of which, 46% were males and 54% were females. Successful clearance of CBD with balloon sweep, dormia basket, CBD stenting or sphincterotomy alone was done in 38 patients (76%). Nine patients (18%) required repeat ERCP/ more than one sitting for clearance of CBD. Most of the patients had stone size of >10 mm (8 out of 9 patients i.e. 88.89%). Three patients were referred for surgical intervention due to non-retrieval of calculus. All these patients had stone size >15 mm (100%). Conclusions: In our study 94% patients eventually achieved successful clearance with ERCP. Also, the size of the stone was an independent risk factor that affected the outcome of ERCP.